Pair interaction potential of particles in two component plasma - Moldabekov, Zh.A.; Ramazanov, T.S.; Dzhumagulova, K.N. (Recent Contributions to Physics, 2012)
The interaction of charged particles in dense plasmas, in which quantum effects are important was investigated on the basis of comparison of the quantum-mechanical Slater sum and the classical Boltzmann factor. On the basis of numerical result and spline approximation an analytical expression for the pair interaction potential between charged particles in a two-component plasma was obtained. This potential takes into account the effect of diffraction. The potential in temperature region of and density region of is considered. It was found that in the limit of high temperatures and densities the results have a good agreement with well known models of Deutsch and Kelbg.